1978
DOI: 10.1063/1.1135470
|View full text |Cite
|
Sign up to set email alerts
|

Ten-microsecond pulsed molecular beam source and a fast ionization detector

Abstract: We describe a pulsed gas valve which we have developed for use as a molecular beam source. In order to observe the performance of the pulsed beam source, we also have developed an ionization detector with a rise time of about 1 micros. The pulsed valve produces very intense supersonic molecular beam pulses of about 10 micros duration for light gases such as H2 and He, and of somewhat longer duration for heavier gases. As a new tool for the study of molecular collisions, the pulsed beam technique offers substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(62 citation statements)
references
References 13 publications
0
56
0
6
Order By: Relevance
“…Pioneering work by Gentry and Giese [7] demonstrated an elegant, tuning fork valve mechanism that produced $10 s pulses of He molecular beams, with water cooling of the valve body. Corat et al [8] later demonstrated a different electromagnetic actuator in which a static coil repels a metallic flyer plate.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work by Gentry and Giese [7] demonstrated an elegant, tuning fork valve mechanism that produced $10 s pulses of He molecular beams, with water cooling of the valve body. Corat et al [8] later demonstrated a different electromagnetic actuator in which a static coil repels a metallic flyer plate.…”
Section: Introductionmentioning
confidence: 99%
“…Many designs of pulsed beam sources are based on various actuating mechanisms (mechanical [6], Lorenz force [7][8][9], Piezo driver [10,11], or electromagnetic [12][13][14][15][16][17]). Several years ago we introduced a shaped nozzle, which combined with a high pressure fast-acting pulsed valve enabled us to reach high beam intensities and lower jet temperatures than what was previously available [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The translational degrees of freedom are cooled, as are the internal degrees of freedom of the molecules. While the first beams were continuous, the method was later extended by using pulsed valves with short opening times [43,44]. The individual pulses could then be made very intense, without the gas load becoming excessive.…”
Section: Beams Of Cold Polar Radicalsmentioning
confidence: 99%